Healthcare provision for insect venom allergy patients during the COVID-19 pandemic - Worm, Margitta; Ballmer-Weber, Barbara; Brehler, Randolf; Cuevas, Mandy; Gschwend, Anna; Hartmann, Karin; Hawranek, Thomas; Hötzenecker, Wolfram; Homey, Bernhard; Jakob, Thilo; Novak, Natalija; Pickert, Julia; et al. (Allergo journal international, 2020)
The population prevalence of insect venom allergy ranges between 3-5%, and it can lead to potentially life-threatening allergic reactions. Patients who have experienced a systemic allergic reaction following an insect sting should be referred to an allergy specialist for diagnosis and treatment. Due to the widespread reduction in outpatient and inpatient care capacities in recent months as a result of the COVID-19 pandemic, the various allergy specialized centers in Germany, Austria, and Switzerland have taken different measures to ensure that patients with insect venom allergy will continue to receive optimal allergy care. A recent data analysis from the various centers revealed that there has been a major reduction in newly initiated insect venom immunotherapy (a 48.5% decline from March-June 2019 compared to March-June 2020: data from various centers in Germany, Austria, and Switzerland). The present article proposes defined organizational measures (e.g., telephone and video appointments, rearranging waiting areas and implementing hygiene measures and social distancing rules at stable patient numbers) and medical measures (collaboration with practice-based physicians with regard to primary diagnostics, rapid COVID-19 testing, continuing already-initiated insect venom immunotherapy in the outpatient setting by making use of the maximal permitted injection intervals, prompt initiation of insect venom immunotherapy during the summer season, and, where necessary, using outpatient regimens particularly out of season) for the care of insect venom allergy patients during the COVID-19 pandemic.